Carl Spaatz papers - Spaatz, Carl, 1891-1974.; Eaker, Ira, 1896-1987.; Hopper, Bruce C. (Bruce Campbell), 1892-1973.
Part I of the Spaatz papers consists of correspondence, diaries, cables, reports, research notes, typescripts of articles and speeches, flight records, personnel file, and miscellaneous papers spanning from 1910 to 1953 and chiefly for the period 1942-1948. Includes material relating to Spaatz's tenure as commander in chief of the U.S. Strategic Air Forces in Europe (1944) and in Japan (1945), as commanding general of the U.S. Army Air Forces (1946), and as chief of staff of the U.S. Air Force (1947-1948); correspondence and reports of Gen. Ira Eaker; and records of the U.S. Strategic Air Forces, including those of its Historical Section and of Bruce C. Hopper.
Correspondents include Henry Harley Arnold, Omar Nelson Bradley, Jacqueline Cochran, Alexander P. De Seversky, Ira Eaker, Dwight D. Eisenhower, Hugh Johnston Knerr, Frank Purdy Lahm, Curtis E. LeMay, Robert A. Lovett, Ted Mack, George C. Marshall, William Mitchell, Robert Porter Patterson, John W. Snyder, Henry Lewis Stimson, Nathan F. Twining, Hoyt Sanford Vandenberg, Jack Warner, and Thomas D. White.
Part II of the collection consists of correspondence, speeches, writings, family and biographical material, and other papers spanning from 1915 to 1981 (chiefly 1948-1963) relating mostly to Spaatz's activities in retirement. Includes material on Operation Torch (1942) in North Africa and Operation Overlord (1944) in Normandy during World War II. Correspondents include Frederick L. Anderson, Eleanor Pool Arnold, Leo Cherne, Ira Eaker, Dwight D. Eisenhower, Curtis E. LeMay, Richard M. Nixon, Elwood R. Quesada, Stuart Symington, and Harry S. Truman.
Library of Congress Prints and Photographs Division.
Army and Air Force officer. Full name: Carl Andrew Spaatz.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Anderson, Frederick L., -- 1905-1969 -- Correspondence; Arnold, Eleanor Pool -- Correspondence; Arnold, Henry Harley, -- 1886-1950 -- Correspondence; Bradley, Omar Nelson, -- 1893-1981 -- Correspondence; Cherne, Leo, -- 1912- -- Correspondence; Cochran, Jacqueline -- Correspondence; De Seversky, Alexander P. -- 1894-1974 -- Correspondence; Eisenhower, Dwight D. -- 1890-1969 -- Correspondence; Knerr, Hugh Johnston, -- 1887-1971 -- Correspondence; Lahm, Frank Purdy, -- 1877-1963 -- Correspondence; LeMay, Curtis E. -- Correspondence; Lovett, Robert A. -- 1895-1986 -- Correspondence; Mack, Ted -- Correspondence; Marshall, George C. -- 1880-1959 -- Correspondence; Mitchell, William, -- 1879-1936 -- Correspondence; Nixon, Richard M. -- 1913-1994 -- Correspondence; Patterson, Robert Porter, -- 1891-1952 -- Correspondence; Quesada, Elwood R. -- 1904- -- Correspondence; Snyder, John W. -- 1895-1985 -- Correspondence; Stimson, Henry L. -- 1867-1950 -- Correspondence; Symington, Stuart, -- 1901-1988 -- Correspondence; Twining, Nathan F. -- 1897-1982 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Vandenberg, Hoyt Sanford, -- 1899-1954 -- Correspondence; Warner, Jack, -- 1916- -- Correspondence; White, Thomas D. -- 1901-1965 -- Correspondence; United States. -- Air Force; United States. -- Army Air Forces; United States Strategic Air Forces in Europe; Operation Overlord; Operation Torch, 1942.; World War, 1939-1945 -- Aerial operations; World War, 1939-1945 -- Campaigns -- Africa, North; World War, 1939-1945 -- Campaigns -- France -- Normandy; Air Force officers; Army officers